Efektivitas Ekstrak Stevia (Stevia Rebaudiana) dalam Menurunkan Kadar Glukosa Darah: Suatu Tinjauan Literatur - Okta Piola; Dia Septiani (Jurnal Sehat Mandiri, 2025)
Diabetes Mellitus (DM) is a chronic disease with a steadily increasing global prevalence, creating an urgent need for effective blood glucose management strategies. One potential alternative is stevia (Stevia rebaudiana) leaf extract, which contains the main components stevioside and rebaudioside. This review aims to evaluate the effectiveness of stevia as an antidiabetic agent based on current literature analysis. Data were obtained through searches on Google Scholar and PubMed using inclusion criteria: original articles, published within the last 10 years, and focusing on the antidiabetic effects of stevia. The results indicate that stevia extract significantly reduces blood glucose levels, improves insulin sensitivity, and exhibits antioxidant properties through mechanisms involving genetic regulation, enhanced enzymatic activity, and reduced inflammation. In conclusion, stevia shows potential as a natural sweetener as well as a complementary therapy in diabetes management, offering additional benefits for lipid profile improvement and cardiovascular protection with minimal side effects. To ensure its long-term safety and efficacy, further human clinical trials with adequate design, extended follow-up periods, and the development of innovative formulations such as nano-stevia are recommended to enhance bioavailability.